From the editors - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
From the Editors CLIL AT UNIVERSITY: RESEARCH AND DEVELOPMENTS In recent times, the relevance of CLIL (Content and Language Integrated Learning) at most educational levels, especially in the university world, has experienced an exponential increase, as recent publications show (Doiz et al. 2013, Fortanet-Gómez 2013, Llinares et al. 2012, or Smit and Dafouz 2012a, among others). Teaching in English seems to be a popular topic nowadays, but it is also a need. The articles included in this issue show three main common features of CLIL and its role in today's higher education: the process of internationalization of the educational system, the need for a language policy, and the fact that English for Specific Purposes (ESP) as a field of research and teaching as well as ESP practitioners are all very much concerned with CLIL.